Apricot fruits respiration intensity in dependence on the method of their treatment by antioxidant composition AKM - Соколова, В. М. (Scientific Progress & Innovations, 2012)
It is established that the studied methods of processing the apricot fruit is the most effective way to spray the fruit with a solution of antioxidant compositions AKM before harvest, which provides forming on the apricots surface film of uniform thickness, which reduces the respiration intensity of fruits in 1,4-1,5 times.